Simulation-based stress testing of banks' regulatory capital adequacy - Samu Peura; Esa Jokivuolle (Bank of Finland, 2003)
Banks' holding of reasonable capital buffers in excess of minimum requirements could alleviate the procyclicality problem potentially exacerbated by the rating-sensitive capital charges of Basel II. Determining the required buffer size is an important risk management issue for banks, which the Basle Committee (2002) suggests should be approached via stress testing.We present here a simulation-based approach to stress testing of capital adequacy where rating transitions are conditioned on business-cycle phase and business-cycle dynamics are taken into account.Our approach is an extension of the standard credit portfolio analysis in that we simulate actual bank capital and minimum capital requirements simultaneously.Actual bank capital (absent mark-to-market accounting) is driven by bank income and default losses, whereas capital requirements within the Basel II framework are driven by rating transitions.The joint dynamics of these determine the necessary capital buffers, given bank management's specified confidence level for capital adequacy.We provide a tentative calibration of this confidence level to data on actual bank capital ratios, which enables a ceteris-paribus extrapolation of bank capital under the current regime to bank capital under Basel II.
URN:NBN:fi:bof-20140807595
Keywords: G21; G32; 330; Basel II; Pillar 2; bank capital; stress tests; procyclicality